Implementasi Corporate Social Responsibility pada Hotel Puri Santrian Sanur Bali - Nadiawati, Ni Made Yuni Sri; Budiasih, I G. A. N. (E-Jurnal Akuntansi, 2021)
The implementation of CSR is considered to benefit the hospitality industry, which will impact on increasing visitor loyalty. One of the CSR awards in Bali is Tri Hita Karana (THK Award). Puri Santrian, one of the participating hotels, is a participant in the Tri Hita Karana Award. The purpose of this research is to know the implementation of CSR in Puri Santrian Hotel. This method of research uses qualitative methods. The location of this research is Hotel Puri Santrian. The informant chosen is HRD staff, Engineering staff, Accounting staff. The interview shows the Santrian Palace has implemented CSR based on the well-established philosophy of Tri Hita Karana. However, in the part of the given assistance can be more varied. Keywords: Corporate Social Responsibility, Tri Hita Karana, Implementation Of CSR Practices.